Carbonate system biogeochemistry in a subterranean estuary – Waquoit Bay, USA. (15th April 2017) - Liu, Qian; Charette, Matthew A.; Breier, Crystaline F.; Henderson, Paul B.; McCorkle, Daniel C.; Martin, William; Dai, Minhan
Abstract: Quantifying carbon fluxes associated with submarine groundwater discharge (SGD) remains challenging due to the complex biogeochemistry of the carbonate system in the subterranean estuary (STE). Here we conducted time series measurements of total alkalinity (TAlk) and dissolved inorganic carbon (DIC) in a well-studied coastal aquifer (Waquoit Bay, Massachusetts, USA). Groundwater samples were collected monthly from May 2009 to June 2010 across the freshwater-saltwater mixing zone of the Waquoit Bay (WB) STE. The concentrations of both TAlk and DIC in zero-salinity groundwater were variable, but were lower than those in the bay water ( S ∼ 28). DIC underwent slightly non-conservative mixing between low and intermediate salinities while there was an apparent additional DIC source at high salinity (>20) in all seasons. TAlk concentrations exhibited even stronger variations, with evidence of both production and consumption in high salinity zones, and consistent TAlk consumption at intermediate salinity in summer and fall (June–December, 2009). The increases in DIC and TAlk at high salinity were attributed to aerobic respiration and denitrification in WB sediments during bay water recharge of the STE. We infer that the loss of TAlk at intermediate salinity reflects H + production as reduced compounds (e.g. Fe 2+ ) are oxidized within the STE. In terms of impacts on surface water inorganic carbon budgets, the SGD-derived DIC flux was mainly controlled by seasonal changes in SGD while a combination of TAlk concentration variability and SGD drove the TAlk flux. SGD-derived DIC, aqueous CO2, and H + fluxes to the bay were ∼40–50% higher in summer vs. in winter, a result of enhanced marine groundwater flux and significant TAlk removal (proton addition) during periods of high seawater intrusion. Furthermore, the SGD-derived DIC flux was consistently greater than TAlk flux regardless of season, indicating that SGD serves to reduce the CO2 buffering capacity of surface water. Our results highlight the importance of seasonality and subsurface biogeochemical processes on the subterranean estuary carbonate system and the resulting impact on SGD-derived TAlk, DIC, aqueous CO2, and H + fluxes to the coastal ocean.